2019
DOI: 10.3389/fneur.2019.01062
|View full text |Cite
|
Sign up to set email alerts
|

Premorbid Alterations of Spontaneous Brain Activity in Elderly Patients With Early Post-operative Cognitive Dysfunction: A Pilot Resting-State Functional MRI Study

Abstract: Background: Elderly patients with pre-existing cognitive impairment are susceptible to post-operative cognitive dysfunction (POCD). In this study, we investigated whether there is pre-existing local homogeneity and functional connectivity alteration in the brain before surgery for POCD patients as compared to that in non-POCD patients.Methods: Eighty elderly patients undergoing major thoracic or abdominal surgeries were recruited. Resting-state functional MRI was scanned at least 1 day before surgery. Neuropsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Previous studies have shown that the diagnosis of SAE relies on questionnaires such as the Confusion Assessment Method for the ICU, as well as delirium screening tools ( Feng et al, 2019 ; Klawitter et al, 2020 ). Currently, rs-fMRI is gaining growing popularity in the clinical evaluation of cognitive impairment such as Alzheimer’s disease, post-traumatic stress disorder, and post-operative cognitive dysfunction ( Herringa, 2017 ; Zhang et al, 2019 ), but studies on its use in SAE patients are still limited. In our study, we found significantly higher ALFF values in the right CA-1, left FC, and HR in SAE rats at 7 days post CLP surgery by rs-fMRI.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the diagnosis of SAE relies on questionnaires such as the Confusion Assessment Method for the ICU, as well as delirium screening tools ( Feng et al, 2019 ; Klawitter et al, 2020 ). Currently, rs-fMRI is gaining growing popularity in the clinical evaluation of cognitive impairment such as Alzheimer’s disease, post-traumatic stress disorder, and post-operative cognitive dysfunction ( Herringa, 2017 ; Zhang et al, 2019 ), but studies on its use in SAE patients are still limited. In our study, we found significantly higher ALFF values in the right CA-1, left FC, and HR in SAE rats at 7 days post CLP surgery by rs-fMRI.…”
Section: Discussionmentioning
confidence: 99%
“…To name one landmark study included in the meta-analysis, the International Study of Post-Operative Cognitive Dysfunction (ISPOCD 1), found that among 1011 older surgical patients recruited in eight European countries and the USA, patients with more than a high school education had even a halved risk of POCD at one week after surgery compared with patients with less than high school education ( Moller et al 1998 ). Studies from various European and Asian countries and the USA that were not included in the 2017 meta-analysis ( Grichnik et al 1999 ) or published thereafter ( Bendikaite and Vimantaite 2020 ; Ehsani et al 2020 ; Huang et al 2020a ; Klinger et al 2019 ; Li et al 2020 ; Wang et al 2018 ; Yuhe et al 2020 ; Zhang et al 2019 ; Zhou et al 2020 ) too, consistently indicate that patients with a lower educational level are at increased POCD risk at discharge ( Zhang et al 2019 ) within days of surgery ( Ehsani et al 2020 ; Li et al 2020 ; Zhao et al 2020 ; Zhou et al 2020 ) but also during six to 12 weeks after surgery ( Grichnik et al 1999 ; Yuhe et al 2020 ). The fact that observations extend to several months after surgery is important because studies on POCD with longer follow-up periods offer preferred scope for conclusions: during shorter follow-up periods immediate effects of surgery on brain function including a potential influence of POD can prevail.…”
Section: Cognitive Epidemiology In a Surgical Settingmentioning
confidence: 99%
“…Advancements in magnetic resonance imaging (MRI) have provided a useful tool to noninvasively capture detailed alterations in brain structure and function [9]. In our pilot study with small sample size, we found that there were differences of regional homogeneity in the right hippocampus/parahippocampus between the DNR patients and non-DNR patients (Gaussian random field corrected) [10].…”
Section: Introductionmentioning
confidence: 75%